Evaluation of the Behavioral Effect of Psychostimulants in Children with Autism Spectrum Disorder: A Cross-Sectional Study - Silva, Francisca de Azevedo e; P. Morais, João; Mira Coelho, Alda (Neuropediatrics, 2024)
Background Autism spectrum disorder (ASD) is often accompanied by comorbid conditions such as attention deficit hyperactivity disorder and epilepsy. In this context, patients are often treated with psychostimulants in an attempt to control behavioral symptoms. This study aims to understand the behavioral effects of psychostimulants in children with ASD and investigate if interictal epileptiform discharges on electroencephalogram (EEG) can act as a modifying factor in this behavior.Methods Sixty-eight patients with ASD who were being accompanied in the Department of Child and Adolescent Psychiatry of the Centro Hospitalar Universitário de São João and had previously done an EEG assessment answered a questionnaire regarding their behavioral response to psychostimulants.Results In total, 47.4% of patients reported improved agitation, 56.1% enhanced concentration, and 8.8% improved sleep. Conversely, 28.1% experienced worsened agitation, 15.8% worsened concentration, and 17.5% worsened sleep. The remaining reported no alterations. The age of diagnosis correlated significantly with improved agitation, with a higher diagnosis age being associated with a higher probability of improvement. Extended-release methylphenidate and genetic variations were significantly associated with worsening of agitation. Regarding speech, 86% exhibited no changes, while 14% showed alterations, mostly, 87.5%, characterized as negative. For other behavioral alterations, 45.6% reported negative changes, 3.5% reported positive changes, and 50.9% reported no additional alterations. Female gender was significantly associated with other negative behavioral changes. A significant correlation was found between treatment duration and the probability of improvement in agitation, concentration, and other behavioral changes.
Keywords: autism spectrum disorder; psychostimulants; behaviors; interictal epileptiform discharges; EEG